The impact of work related physical activity and leisure physical activity on the risk and prognosis of neck pain – a population based cohort study on workers. Issue 1 (December 2016) - Palmlöf, Lina; Holm, Lena; Alfredsson, Lars; Magnusson, Cecilia; Vingård, Eva; Skillgate, Eva
Abstract Background The effect of physical activity on risk and prognosis for neck pain has been studied earlier with inconclusive results. There is a need for large prospective studies on the subject. The aim of this study was to investigate if work related physical activity and physical activity during leisure time are of importance for the risk and prognosis of neck pain in men and women. Methods We used the Stockholm Public Health Cohort and formed two sub-cohorts of the working population based on data from 2002. Cohort I (risk cohort) included persons without neck pain (n  = 4681), and cohort II (prognostic cohort) included persons with occasional neck pain (n  = 6820) during the previous six months. Both cohorts were assessed for the outcome long duration troublesome neck pain (LDNP) in 2007. The exposures and potential confounders were assessed through a questionnaire in 2002. The question regarding work related physical activity over the past 12 months had five answering categories ranging from "sedentary" to"heavy". The question regarding leisure physical activity for the past 12 months had five answering categories ranging from "sedentary" to "regular physical activity". LDNP in 2007 was defined as having had troublesome neck pain lasting ≥ 3 consecutive months during the previous five years. Associations between work related physical activity and LDNP, as well as leisure physical activity and LDNP, were investigated by multivariable logistic regression, considering potential confounding factors. Results In cohort I (risk cohort) we found an association between leisure physical activity and LDNP. In cohort II (prognostic cohort) we found no association between the exposures and the outcome. Conclusion The results suggest that leisure physical activity has a protective effect on the risk of developing LDNP in a population free from neck pain. It did not, however, affect the prognosis of occasional neck pain. Neither the risk nor the prognosis of neck pain was affected by work related physical activity in this study.